Terahertz Dual-Band Metamaterial Biosensor for Cervical-Cancer Diagnostics - Musa N. Hamza; Mohammad Alibakhshikenari; Bal Virdee; Muhamad A. Hamad; Salahuddin Khan; Slawomir Koziel; Ernesto Limiti (IEEE Photonics Journal, 2024)
This study highlights the potential of employing terahertz metamaterial structures as dual-band biosensors for the early detection of cancerous biological tissue. The fundamental principle leveraged here is the alteration of the effective dielectric constant of biological tissue by cancerous cells. The change in the dielectric constant, in turn, induces a shift in the resonance frequency of the metamaterial sensor. One notable advantage of the terahertz metamaterial sensor is its relatively compact size compared to other sensor types, as its dimensions are independent of the wavelength. This property translates into a requirement for a much smaller biopsy sample, facilitating less invasive testing procedures. Beyond the size advantage, the proposed biosensor demonstrates efficacy in detecting abnormalities within biological tissue.